Olu & Greta - Ejaita, Diana (Rise x Penguin Workshop, an imprint of Penguin Random House LLC, 2021)
Two cousins--one in Lagos, Nigeria, and the other in Milan, Italy--have different lives, but they share a dream of meeting and being together.